Current trends in advanced compound materials selected, peer reviewed papers from the National Conference on Current Trends in Advanced Materials, January 29-30, 2016, Hoshangabad, India - Arya, Balwant S.; Jha, Prafulla K.; Sanyal, Sankar P. (Journal of Metastable and Nanocrystalline Materials, 2016)
Selected, peer reviewed papers from the National Conference on Current Trends in Advanced Materials, January 29-30, 2016, Hoshangabad, India